Pengaruh Biaya Operasional Terhadap Profitabilitas Pada PT Tropical di Jakarta - Widodo, Adji; Nazir, Ahmad; Sunarsi, Denok (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to determine the effect of Operational Costs on Profitability at PT. Tropical in Jakarta. The method used is explanatory research with samples of the financial statements of PT. Tropical for 5 (five) years, namely 2014-2018. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study, the Operational Cost variable obtained a minimum of 71.2 billion and a maximum of 89.2 billion and an average of 84.4 billion with a standard deviation of 75.1 billion. Profitability is obtained at a minimum of 7.12% and a maximum variance of 8.51% and an average of 8.04% with a standard deviation of 0.54%. Operational costs have a positive and significant effect on profitability with the regression equation Y = 2.574 + 6.479X, and a correlation coefficient value of 0.886 or having a strong level of relationship with a determination value of 78.5%. Hypothesis testing obtained a significance of 0.045 <0.05.